THE EFFECT OF REGIONAL ORIGINAL INCOME AND ACCURACY OF SHOPPING ALLOCATION ON REGIONAL ECONOMIC GROWTH IN LAMONGAN - I Made Bagus Dwiarta; Fachrudy Asjari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to examine the effect of local revenue and the accuracy of expenditure allocation on economic growth of a region. The independent variables of this study are regional original income and the accuracy of expenditure allocation while the dependent variable is economic growth. This study uses a quantitative approach. Technical data analysis in this study uses multiple linear regression models. The results of this study are that regional original income has no significant effect on the economic growth of Lamongan Regency in 2013-2017 and the accuracy of expenditure allocation does not significantly influence the economic growth of Lamongan Regency in 2013-2017.